A new high step-up DC-DC converter for photovoltaic application: switch inductor cell combined with voltage doubler circuit - Akter, Khadiza; Motakabber, S. M. A.; Alam, A. H. M. Zahirul; Yusoff, Siti Hajar (IEEE, 2022)
A new model of switch inductor (SL) combined with a voltage doubler-employed DC-DC step-up converter has been developed here to get optimum output from the solar photovoltaic cell. The voltage transformation ratio of the proposed circuit is almost six times higher than the input voltage. The high step-up ratio is obtained without worsening the transformation efficiency of the converter. The functionality of the suggested configuration has been compared with current, advanced DC-DC converters incorporated with a PV source. The proposed design performs better than existing designs regarding voltage gain and efficiency. Maximum Power Point Tracking (MPPT), an approach that relies on the Perturb and Observe (P&O) algorithm, has been used to ensure the optimum performance attainable from Photovoltaic panels. The employment of MPPT controllers does not deteriorate the performance of the proposed design; instead, 96% conversion efficiency has been achieved. Simulation of the proposed and existing topology have been carried out in PSIM and Simulink environments.